Innate antipredator behavior can promote infection in fish even in the absence of predators. (12th November 2019) - Mikheev, Victor N; Pasternak, Anna F; Morozov, Andrew Yu; Taskinen, Jouni
Abstract: Natural enemies—predators and parasites—largely shape the dynamics of ecosystems. It is known that antipredator and antiparasite defense can be mutually conflicting, however consequences of this trade-off for the regulation of infection burden in animals are still poorly understood. We hypothesize that even in the absence of cues from predators, innate antipredator behavior ("ghost of predation past") interferes with defense against parasites and can enhance the infection risk. As a case study, we explore interactions between a commercial species, the rainbow trout Oncorhynchus mykiss, and its parasite, the trematode eye-fluke Diplostomum pseudospathaceum . Fish–parasite interactions were tested in compartmentalized tanks where shelters and parasites were presented in different combinations providing various conditions for microhabitat choice and territorial behavior. Shelters were attractive and contestable despite the absence of predators and presence of parasites. The individuals fighting for shelters acquired more than twice the number of cercariae as compared to those in infected shelter-free compartments. Most infected were subordinate fish with a higher ventilation rate. Fish possessing shelters were less vulnerable to parasites than fighting fish. Grouping reduced the infection load, although less efficiently than sheltering. Our data demonstrate that the innate antipredator behavior can undermine antiparasite tactics of the fish and result in higher infection rates. Using our empirical results, we construct a mathematical model which predicts that enriching the environment in fish farming will be beneficial only when a large number of shelters is provided. Using insufficient number of shelters will increase the parasite burden in the fish. Lay Summary: Conflicting demands of defense against natural enemies increase the risk of parasitism in the presence of predators. We show that even in the absence of predators a built-in antipredator behavior of fish (ghost of predation) may affect parasitism. Grouping and sheltering may reduce not only predation but also infection risk. However, fish fighting for a shelter acquire more parasites due to increased stress and ventilation. We show that there is an optimum number of shelters.